A Critical Review of Scientometrics Epistemology - Gholamreza Fadaie (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The book entitled “Scientometrics Epistemology” has been published in Medium octavo format with 6 chapters and 240 pages. It includes the list of contents, figures, and references, with no index. In this article, the above-mentioned book is criticized, and the critic, while explaining the position of scientometrics, states that scientometrics is originally related to counting, measuring, and representation, and the discussion of creating or relating epistemology to it is not sufficiently justified. The book has been written based on the library method. Scientometrics is actually a technique and method that serve evaluation, which is, in turn, related to management. Naturally, every human being and then research and educational organizations have tried to expand scientometrics and created indicators to compare scientific products based on quantity in order to determine their degree of importance, which is not unrelated to economic and managerial issues.